2019
DOI: 10.1177/1557988319882589
|View full text |Cite
|
Sign up to set email alerts
|

“As I Was Walking Down the Street, Four Strange Guys Came and Took Me Under the Bridge, Where They All Raped Me”: An Interpretative Phenomenological Analysis of the Types of Rape Experienced by Men in South Africa

Abstract: Globally, rape is regarded as the most demoralizing type of trauma, and it has negative implications for victims and their families. Although rape affects the community in general, there is a paucity of literature on rape victimization of men. As a result, the types of rape experienced by them are not understood, and thus it is often difficult to develop contextually relevant interventions to prevent male rape and to support male rape victims. The objective of this study was to first determine and then describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 46 publications
(49 reference statements)
0
31
0
Order By: Relevance
“…Data collection commenced with a pilot study which was conducted with the first three participants to determine the shortcomings from the recruitment strategy, to check whether the participants could easily understand the interview questions and to determine any potential ethical issues that could arise during data collection and thus affect the credibility of the main study. The data collected from the pilot study were included in the data for the main study for data analysis because the same recruitment strategy was used and no ethical issues were identified (Duma, 2006;Duma et al, 2009;Mgolozeli and Duma, 2019). In this study, data collection and data analysis occurred concurrently over four months between August and November 2018.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Data collection commenced with a pilot study which was conducted with the first three participants to determine the shortcomings from the recruitment strategy, to check whether the participants could easily understand the interview questions and to determine any potential ethical issues that could arise during data collection and thus affect the credibility of the main study. The data collected from the pilot study were included in the data for the main study for data analysis because the same recruitment strategy was used and no ethical issues were identified (Duma, 2006;Duma et al, 2009;Mgolozeli and Duma, 2019). In this study, data collection and data analysis occurred concurrently over four months between August and November 2018.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The voluntary participation was also highlighted on the information sheet and a verbal explanation of the study's aim, participants' rights, risks and benefits, and the recruitment strategy was given to participants. All participants were reimbursed with ZAR150 for their travel expenses for the interviews and for their time (Duma et al, 2009;Mgolozeli and Duma, 2019;Sullivan and Cain, 2004).…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Participants were made aware that their participation in the study was voluntary, and they were free to withdraw at any time if they were uncomfortable. Participants were reimbursed with an amount of ZAR150 for their traveling expenses and time as supported by other researchers in the field of sexual violence [6,45,46]. Participants were reassured that their real names would not be made available to any other party during the study and reporting of the research findings; instead, pseudonyms would ensure anonymity and confidentiality.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…This could be related to the fact that homophobic violence is more common in South Africa where perpetrators also use rape to show hatred and disapproval of people who belong to the lesbian, gay, bisexual, transgender, queer and intersex (LGBTQI) community [78][79][80]. A recent study by Mgolozeli and Duma [6] on types of rape experienced by men also found homophobic rape as another type of rape experienced by men in South Africa. Rape is also a form of anti-gay hate crime committed against members of the LGBTQI community, and these victims often choose not to report to the police to avoid disclosing their sexual orientation [81].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation